Mail Art : Osteuropa im Internationalen Netzwerk. - Albrecht, D.; Babenko, Dmitry; Baroni, Vittore; Beke, László; von Berswordt-Wallrabe, Kornelia; Bleus, Guy; Blume, Eugen; Bonari, Adriano; Crozier, Robert; Daligand, Daniel; Diotallevi, Marcello; Dressler, Uwe; et al. (Schwerin : Staatliches Museum Schwerin, 1996)
Artpool ; Bakos, Zoltan ; Beke, László ; Czobor, Sandor ; Lengyal, András ; Pap, Bèla ; Pauer, Gyula ; Takacs, Rudolf ; Tarsasag, A. ; Tóth, Arpad ; Tot, Endre ; Tóth, Gábor ; Tamás, Vaczy Jépont ; Swierkiewicz, Róbert ; Janousek, Miroslav ; Juhasz, Joszef R. ; Klimes, Svatopluk ; Klivar, Miroslav ; Knizak, Milan ; Kocman, Jiri H. ; Mészáros, Otto ; Skrepsky, Vojtech ; Sladek, Ivan ; Valoch, Jiri ; Nekrasius, Jonas ; Nikonova, Rea ; Segay, Serge ; Sutjagin, Wladimir ; ZPAP, BWA & ; Bedkowski, Jacek ; Byszewski, Janusz ; Bzdok, Henryk ; Chadzynski, Waldemar ; Chwalczyk, Jan ; Czechowicz, Belin ; Dudek, Artur ; Dudek-Dürer, Andrzej ; Dziamski, Grzegorz ; Fraczek, Ireneusz ; Gajewski, Henryk ; Gajownik, Marcin ; Golkowska, Wanda ; Janiak, Marek ; Jezierski, Kowale ; Jozefowski, Eugeniusz ; Karwowski, Karol ; Kirko, Andrej ; Kionowski, Stachu ; Kolo, Slawomir ; Kowalski, Krzysztof ; Kumor, Wieslaw ; Kwietniewski, Andrzej ; Marian, Kokuciuk Adam ; Mierunski, Zbyszek ; Muszynski, Roman ; Ojda, Fredo ; Paszkiewicz, Yach ; Petasz, Pawel ; Pietka, Maciej Abel ; Office, Postal ; Rogalski, Piotr ; Ropiecki, Waclaw ; Rupocinski, Robert ; Rostocki, Alexander ; Rypson, Piotr ; Sapijaszko, Grzegorz ; Schulz, Tomasz ; Sikorski, Tomasz ; Skiba, Christopher ; Slusarski, Andrzej ; Sobolewski, A.M. ; Sojka, Wojtek ; Szymczak, Krzysztof ; Szubzda, Andrzej ; Wasilewski, Marcin ; Wielgosz, Andrzej ; Zwara, H. Agnes ; Rares, Pantea ; Kiss, Emilia ; Flondor, Constantin ; Bogdanovic, Nenad ; Dordevic, Goran ; Hlupic, B. ; Kamperelic, Dobrica ; Klancnik, Stane ; Kopse, Miriam ; Lantos, Laszlo ; Malkovic, Slavko ; Masic, Radomir ; Poznanovic, Bogdanka ; Supek, Jaroslav ; Szombathy, Bálint ; Timotjevic, Slavko ; Tisma, Andrej ; Todorovic, Miroljub ; Toman, Tibor ; etc.
Duits & Engels
Mail Art : Osteuropa im Internationalen Netzwerk / Eastern Europe in International Network, Staatliches Museum Schwerin, 21.7. - 15.9.1996 ; Kunsthalle Budapest, 1998
boek